Integrated optimal wind‐resistant design of super‐tall structures with toggle‐brace damper systems - Zhao, Xin; Guo, Junchen; Ma, Haojia; Ding, Kun (The structural design of tall and special buildings, 2020)
Summary With the increasing heights of super‐tall buildings, the natural frequency of these structures approaches the predominant frequency of winds, causing the structures to be more sensitive to wind load. For the safety and economy of these structures, the formulation of a reasonable wind‐resistant design is crucial. In this paper, an optimal design of toggle‐brace damper systems for super‐tall buildings using a damping ratio limit method is presented to obtain the optimal placement, number, and damping coefficient of toggle‐brace dampers under different constraints. The constraints include the additional damping ratio under a 50‐year return period wind, the maximum power of the damper under a 50‐year return period wind, and the maximum output force of a moderate earthquake. The toggle‐brace damper systems improve the structural performance. Hence, the structural components produce design redundancy, which can be optimized using the sequential quadratic programming (SQP) algorithm and a multi‐grade constrained optimal design method to further improve the economic benefits of the structure. Based on the combination of the optimal design method of toggle‐brace damper systems, SQP algorithm, and multi‐grade constrained optimal design method, an integrated optimal wind‐resistant design for toggle‐brace damper systems is proposed. To demonstrate the effectiveness and applicability of this design, a 245‐m super‐tall building is employed as an engineering case.